The association between research funding status and clinical research papers’ citation impact in Japan: A cross-sectional bibliometric study - Morisawa, Fumito; Nishizaki, Yuji; Devos, Patrick; Yanagisawa, Naotake; Matsuyama, Kotone; Homma, Yasuhiro; Ueda, Rieko; Sekine, Miwa; Daida, Hiroyuki; Minamino, Tohru; Sanada, Shoji (Frontiers in Medicine, 2022)
Introduction: Studies have not sufficiently clarified the differences in citation impact between funded and non-funded clinical research papers. Hence, this study seeks to evaluate the relation between research funding status and clinical research papers’ citation impact in different research fields using multiple evaluation indices. Methods: In this cross-sectional bibliometric study, clinical research papers published by core clinical research hospitals in Japan were compared retrospectively in terms of times cited (TC), category normalized citation impact (CNCI), citation percentile (CP), journal impact factor (JIF), the Software to Identify, Manage, and Analyze Scientific Publications (SIGAPS) category, and whether they were the funded clinical research. The association between research funding status or the SIGAPS category and CNCI ≥ 2 was analyzed using logistic regression analysis. Results: 11 core clinical research hospitals published 553 clinical research papers, of which 120 were non-funded and 433 were funded (public institution-funded and industry-funded). The study found that funded clinical research papers (public institution-funded and industry-funded) had significantly higher TC, CNCI, CP, and JIF than non-funded ones [TC: 8 (3–17) vs. 14 (8–31), p < 0.001; CNCI: 0.53 (0.19–0.97) vs. 0.87 (0.45–1.85), p < 0.001; CP: 51.9 (24.48–70.42) vs. 66.7 (40.53–88.01), p < 0.001; JIF: 2.59 (1.90–3.84) vs. 2.93 (2.09–4.20) p = 0.008], while the proportion of A or B rank clinical research papers of the SIGAPS category was not significantly different between the two groups (30.0% vs. 34.9%, p = 0.318). In the logistic regression analysis, having a CNCI ≥ 2 was significantly associated with research funding (public institution-funded and industry-funded) and publication in A or B rank journals of the SIGAPS category [research funding: Estimate 2.169, 95% confidence interval (CI) 1.153–4.083, p = 0.016; SIGAPS category A/B: Estimate 6.126, 95% CI 3.889–9.651, p < 0.001]. Conclusion: Analysis via multiple indicators including CNCI and the SIGAPS category, which allows for a comparison of the papers’ citation impact in different research fields, found a positive relation between research funding status and the citation impact of clinical research papers.